Incidencia de Parto Pretérmino en Mujeres Atendidas en el Servicio de Gineco Obstetricia del Hospital Provincial, Cantón Latacunga, Provincia de Cotopaxi. Enero - Agosto 2008 - Ramos Valencia, Diego Xavier (2010)
This study aimed to identify factors that influence the onset of preterm birth in women treated at the Gynecology and Obstetrics Service of the Latacunga Provincial Hospital, Cotopaxi Province, from January to August 2008, in order to obtain reliable data. This was a descriptive, retrospective, cross-sectional study. A sample of patient medical records constituted 100% of the study population. It was observed that 90% of these births occurred between 33 and <36.6 weeks of pregnancy. Fifty-five percent of preterm births occurred in multiparous women. The maternal age range in which it occurred most frequently was between 18 and 23 years, at 31%, representing a major risk factor. Seventy percent of mothers had only primary education, which influenced the use of prenatal care. Fifty-six percent had fewer than six follow-up visits. Of the 63 patients, the risk factor was not determined in 22% due to a lack of screening upon admission or poor completion of medical records. Due to poor management of medical records at the Hospital, the primary risk factor could not be determined in approximately 14% of the sample studied. It is concluded that some of the most important risk factors for preterm birth are young age, multiparity, and a low educational level, which leads to inadequate prenatal care, accounting for a high percentage (56%) of preterm births. Training of healthcare personnel is recommended to improve care and provide more appropriate medical monitoring.